El derecho al fondo de reserva y su cumplimiento en favor de los trabajadores del sector privado en Guaranda año 2022. - Pazmiño Saltos, Carlos Vicente (2024)
This research work is titled “The right to the reserve fund and its fulfillment in favor of private sector workers in Guaranda in 2022”, I will carry out a doctrinal and legal analysis of the fulfillment of this economic benefit in favor of workers of the private sector in the city of Guaranda. According to legal regulations, the reserve fund is a right that is generated for the benefit of every worker who provides services for more than one year for the same employer, who has the obligation to deliver a sum equivalent to one month of salary or 4 salary for each full year of work after the first year, with the latest legal reform this benefit can be paid monthly at a percentage of 8.33% of the remuneration received by the worker. This economic benefit is linked to the labor protection criterion that considers that each year that passes the worker decreases his workforce, so it is necessary for him to have capitalized savings that he can use at the end of his service time, this It will allow the worker to face and resolve his multiple needs. The reserve fund, being a right fully regulated by the labor law, is on several occasions evaded in its compliance by private employers, and a large number of workers in private entities do not even know that they should receive this benefit and worse still demand its fulfillment. It is also necessary to specify that the governing institution of labor policy in Ecuador does little or nothing to exercise control and verification activities on the effective fulfillment of this economic benefit, which is why this research will analyze the real situation of private workers in the city of Guaranda regarding the enjoyment and fulfillment of this benefit. Being a descriptive research, the descriptive method will be used with the purpose of defining, cataloguing, classifying or characterizing the object of study. As this work constitutes a legal topic, I will use the nomothetic and ideographic methods. The research methodology is qualitative, with the dogmatic and interpretive method of constitutional and legal norms, since through these methods an answer to the 5 problem treated is offered by producing the best possible reconstruction allowed by all the legal material that is available. Keywords: Reserve fund, right, benefit, compliance, workers, private sector, savings.